2012
DOI: 10.1007/s12471-012-0250-5
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic therapy in heart failure

Abstract: Patients with congestive heart failure have a significant risk of stroke due to thromboembolism from the dilated left ventricle. Two relatively small trials suggest that oral anticoagulation with vitamin-K antagonists may reduce this risk when compared with placebo, aspirin or clopidogrel. However, more studies are eagerly awaited. So far, physicians seeing patients with heart failure should decide who needs antithrombotic prophylaxis on a case-by-case basis, especially since most heart failure patients have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Early studies and post hoc analyses of large clinical trials have demonstrated a reduction in thromboembolic events, risk of stroke, and mortality. In contrast, recent underpowered prospective controlled studies found no benefit in the use of warfarin in patients with systolic HF and normal sinus rhythm 36,37 . The low to moderate risk of thromboembolism and the questionable benefit of anticoagulation need to be weighed against the potential for hemorrhagic complication.…”
Section: Discussionmentioning
confidence: 98%
“…Early studies and post hoc analyses of large clinical trials have demonstrated a reduction in thromboembolic events, risk of stroke, and mortality. In contrast, recent underpowered prospective controlled studies found no benefit in the use of warfarin in patients with systolic HF and normal sinus rhythm 36,37 . The low to moderate risk of thromboembolism and the questionable benefit of anticoagulation need to be weighed against the potential for hemorrhagic complication.…”
Section: Discussionmentioning
confidence: 98%
“…Over the past years, there is increasing evidence about the brainheart interaction with major potential implications for treatment of cardiovascular diseases. For instance, cerebrovascular accidents (CVAs) and transient ischaemic attacks (TIAs) are frequently caused by cardiac arrhythmias and/or congestive heart failure [5,6]. In particular atrial fibrillation may result in cognitive disorders preceding the occurrence of TIAs or CVAs [7][8][9][10].…”
mentioning
confidence: 99%
“…2,21,22 BT is the period from broken capillaries to bleeding discontinuation. The process could be either intrinsic or extrinsic coagulation, depending on the pathways of initiating prothrombin activator formation and other factors, which ultimately activate factor X, leading to thrombus formation and coagulation.…”
Section: Discussionmentioning
confidence: 99%